Textile based electrodes for ECG and EMG measurements - Catarino, André P. (2017)
Biopotential signals are an important tool for monitoring our health and thanks to the evolution of technology, they are being increasingly used in several areas. There are however some problems with conventional electrodes such as irritation that need to be surpassed and textile electrodes may represent a good alternative. This paper proposes a design approach for textile based electrodes developed by our research group, in which the construction of the electrodes is based on 3D surface design of weft knitted structures, which increases thickness and allows to improve the permanent contact between electrode and skin, thus contributing for the solution of one of the problems identified by the research community.